2021
DOI: 10.1016/j.cmi.2020.10.034
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection: the environmental endurance of the virus can be influenced by the increase of temperature

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 9 publications
1
41
0
Order By: Relevance
“…The effects of meteorological factors, particularly temperature and humidity, on COVID-19 spread have been widely investigated since the beginning of the pandemic. In fact, agents that cause respiratory tract infections usually have their maximum infection potential in cold seasons, and experimental studies have shown that increasing temperature and decreasing humidity decreases SARS-CoV-2 survival on surfaces ( Biryukov et al, 2020 ; Magurano et al, 2020 ). However, although the results of published studies on this issue are rather homogeneous, the overall evidence for a role of these factors on COVID-19 spread is still weak, due to the low quality of most studies ( Mecenas et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of meteorological factors, particularly temperature and humidity, on COVID-19 spread have been widely investigated since the beginning of the pandemic. In fact, agents that cause respiratory tract infections usually have their maximum infection potential in cold seasons, and experimental studies have shown that increasing temperature and decreasing humidity decreases SARS-CoV-2 survival on surfaces ( Biryukov et al, 2020 ; Magurano et al, 2020 ). However, although the results of published studies on this issue are rather homogeneous, the overall evidence for a role of these factors on COVID-19 spread is still weak, due to the low quality of most studies ( Mecenas et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies tested virus persistence on surfaces of common use such as plastic, glass, stainless steel, wood, paper, copper and cloth [ 7 , 8 , 9 , 10 ]. According to these studies, SARS-CoV-2 stability seems to be influenced by the characteristics of the different materials but also by environmental conditions such as temperature, pH and humidity [ 8 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, temperate likely directly affects social distancing, since people are more inveigled to spend time outdoor, thus reducing the higher risk attributable to indoor viral transmission (17). Second, longer sunlight exposure and higher outdoor temperature have also been associated with greater extent of viral inactivation (18, 19). Finally, reliable evidence has been provided that virus-containing droplets could travel 3-fold slower in higher temperature environments (20), thus consistently mitigating their air propagation and infective potential.…”
Section: Discussionmentioning
confidence: 99%